2003
DOI: 10.1046/j.1360-2276.2003.01139.x
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Schistosoma haematobium and Schistosoma mansoni in humans in north Cameroon

Abstract: Summaryobjectives To analyse the relationships between the frequency of ectopic localizations of Schistosoma haematobium and S. mansoni eggs.methods Studies were conducted in 11 villages in north Cameroon, around Bessoum, a village where an epidemic of bloody diarrhoea caused by S. mansoni occurred in 1997.results The results revealed infection prevalence rates of 70.5% for S. haematobium and 30.8% for S. mansoni. Interestingly, S. mansoni eggs were found in 14.5% of the urine samples and S. haematobium eggs i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
57
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 17 publications
3
57
3
Order By: Relevance
“…In addition to affecting the prevalence and intensity of human infections, inter-specific parasite interactions during mixed species infections may, however, also be predicted to impact host morbidity directly. In one of the few studies to consider this, Cunin et al (2003) in Cameroon, for example, reported an apparent lowering of S. mansoni- induced morbidity (hepatomegaly and splenomegaly morbidity, as determined through clinical palpation) in mixed infections with S. haematobium relative to that observed for S. mansoni single infections [6]. The authors suggested that this lowering effect on liver morbidity could be due to S. haematobium males mating with S. mansoni females (which cannot successfully hybridize) and the subsequent eggs produced from such couplings passing to the urinary oviposition site, thereby reducing the amount of classical S. mansoni -induced morbidity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to affecting the prevalence and intensity of human infections, inter-specific parasite interactions during mixed species infections may, however, also be predicted to impact host morbidity directly. In one of the few studies to consider this, Cunin et al (2003) in Cameroon, for example, reported an apparent lowering of S. mansoni- induced morbidity (hepatomegaly and splenomegaly morbidity, as determined through clinical palpation) in mixed infections with S. haematobium relative to that observed for S. mansoni single infections [6]. The authors suggested that this lowering effect on liver morbidity could be due to S. haematobium males mating with S. mansoni females (which cannot successfully hybridize) and the subsequent eggs produced from such couplings passing to the urinary oviposition site, thereby reducing the amount of classical S. mansoni -induced morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…The aim of the current study was to test if the hypothesis that liver morbidity in mixed schistosome species infections is lower relative to that observed for S. mansoni single infections [6], can be generalized in different environmental settings within sub-Saharan Africa such as Mali. Furthermore, while previous studies were restricted to clinical examination and palpation of hepatomegaly and splenomegaly, the present study also incorporates detailed ultrasonography (US) to determine schistosome-specific morbidity in the liver and bladder.…”
Section: Introductionmentioning
confidence: 99%
“…Helminths are macroparasites that reproduce sexually within the definitive host, where they can persist for many years, whereas protozoa are microparasites that are capable of direct reproduction within the host, often at high rates, and cause relatively shortlived infection. 16 Helminth infections are well-known to elicit a Type 2 (Th2) noninflammatory T-cell response, 17 a hallmark of which is IgE elevation with eosinophilia, and which may be strong enough to exert biasing effects on concomitant infections 18,19 as well as host response to Th1-mediated chronic infections, [20][21][22] including intracellular parasites. 23 By contrast, many protozoa, like bacteria, act through manipulation of Th-1 pathways.…”
Section: Introductionmentioning
confidence: 99%
“…, and that competition for mates and 'over-spill' can result in hybridisation 55 . Taking the different efficacy of PZQ in the two main human schistosome species that are co-endemic in some African regions (S. mansoni and S. haematobium), hybridisation and its effects on pathology/morbidity require monitoring and further investigation.…”
mentioning
confidence: 99%